Quantitative analysis of diffusion weighted imaging in rectal cancer during radiotherapy using a magnetic resonance imaging integrated linear accelerator. (July 2022) - Ingle, Manasi; Blackledge, Matthew; White, Ingrid; Wetscherek, Andreas; Lalondrelle, Susan; Hafeez, Shaista; Bhide, Shreerang
Highlights: Magnetic resonance imaging integrated platforms (MR-Linac) allows for on-treatment imaging. Diffusion weighted imaging (DWI) taken during treatment can measure biological response. Median apparent diffusion coefficient (ADC) from first fraction to last fraction increases in rectal cancer patients. No change is seen in median ADC value from first fraction to last fraction in normal tissue. DWI demonstrates promise in its ability to determine response to treatment in rectal cancer patients. Abstract: Background and purpose: Magnetic resonance imaging integrated linear accelerator (MR-Linac) platforms enable acquisition of diffusion weighted imaging (DWI) during treatment providing potential information about treatment response. Obtaining DWI on these platforms is technically different from diagnostic magnetic resonance imaging (MRI) scanners. The aim of this project was to determine feasibility of obtaining DWI and calculating apparent diffusion coefficient (ADC) parameters longitudinally in rectal cancer patients on the MR-Linac. Materials and methods: Nine patients undergoing treatment on MR-Linac had DWI acquired using b-values 0, 30, 150, 500 s/mm 2 . Gross tumour volume (GTV) and normal tissue was delineated on DWI throughout treatment and median ADC was calculated using an in-house tool (pyOsirix ®). Results: Seven out of nine patients were included in the analysis; all demonstrated downstaging at follow-up. A total of 63 out of 70 DWI were analysed (7 excluded due to poor image quality). An increasing trend of ADC median for GTV (1.15 × 10 −3 mm 2 /s interquartile range (IQ): 1.05–1.17 vs 1.59 × 10 −3 mm 2 /s IQ: 1.37 – 1.64; p = 0.0156 ), correlating to treatment response. In comparison ADC median for normal tissue remained the same between first and last fraction (1.61 × 10 −3 mm 2 /s IQ: 1.56–1.71 vs 1.67 × 10 −3 mm 2 /s IQ: 1.37–2.00; p = 0.9375). Conclusions: DWI assessment in rectal cancer patients on MR-Linac is feasible. Initial results provide foundations for further studies to determine DWI use for treatment adaptation in rectal cancer.